A Low-Frequency Dielectric Barrier Discharge System Design for Textile Treatment. Issue 1 (2nd January 2016) - Naz, M. Y.; Shukrullah, S.; Ghaffar, A.; Rehman, N. U.; Sagir, M.
Abstract : The ultimate goal of the conducted research was to design and test a simplified and energy efficient low-frequency dielectric barrier discharge reactor for the textile processing industry. For this purpose, a 50 Hz AC source and a variac were used to ionize the ambient air column between two asymmetric conductive electrodes separated by a dielectric layer between them. It was observed that the discharge system with such electrode configuration undergoes an electrical breakdown with large number of shortly lived microdischarges indicating the effectiveness of the model. The variational trend in discharge power and transported charge as a function of AC input voltage and dielectric barrier thickness were also studied in this work. In addition, the spectroscopic investigations were carried out on electron number density and electron temperature as a function of barrier thickness, AC input voltage, and interelectrode air gap. A significant influence of the system input parameters on discharge properties was noticed in these investigations.